Violência e criminalidade no campo: aspectos teóricos e ocorrências de crimes econômicos em Toledo (PR) - Botelho, Rosana Claudia (2024)
The aim of this study was to identify and analyze the impacts suffered by rural producers and their families in the face of economic crime. As methodological procedures, the occurrences of economic crimes in the rural area of Toledo from 2018 to 2022 were surveyed, analyzing their evolution, characteristics and specificities recorded in the police reports (B.O.), through data frequency analysis and the use of logistic regression. Interviews were carried out with 30 rural producers whose police reports had been registered, with the aim of analysing the victims' main feelings about crime. As a result, of the 356 registered occurrences of theft and robbery in rural Toledo, the majority were thefts and a minority were robberies. Regarding the time of day of these occurrences, it was observed that the preference of criminals fell on the night. Saturday recorded the highest number of crimes, followed by Thursday, Tuesday and Sunday. The highest frequency of occurrences was in the second semester of the year (July to December), with the most stolen items being those of higher monetary value. The results of the logistic regression showed that the month of December has a higher probability of thefts and robberies occurring during the night/early morning, compared to other months, as well as the subtraction of tools/utensils. Monday and Friday were the days that decreased the probability of this occurrence during the night/early morning, compared to Sunday. The result of the interviews showed a worrying picture, with the majority of the interviewees expressing feelings of insecurity on their properties. The responses obtained through the questionnaire and interview provided valuable insights into the challenges faced by these communities and pointed to various measures that can be taken to counter rural crime.